Solving resource-constrained construction scheduling problems with overlaps by metaheuristic - Bożejko, Wojciech; Hejducki, Zdzisław; Uchroński, Mariusz; Wodecki, Mieczysław (Journal of Civil Engineering and Management, 2014)
The paper concerns the problem of roadworks scheduling executed in the flow-shop system. Works may be performed parallelly with the acceleration (overlaps) of construction project, i.e. the following work on the assembly line can begin before the completion of the predecessor work. Taking into account the acceleration enables accurate modeling of complex real construction processes. The above fact can greatly shorten the time of realization of construction process which has a direct impact on reducing costs. The considered issue belongs to the class of NP-hard problems. We introduce the new: mathematical model, specific properties as an acceleration tools, as well as two new optimization algorithms for the problem considered: construction and tabu search. The execution of algorithms was illustrated on the example of a case study concerning the construction of roads. They were also verified on the examples taken from the literature and on already completed construction processes. The obtained results are fully satisfactory. The assigned execution times are close to optimal. The presented methods allow its practitioners (both the planners and the managers) to include in the model the acceleration of the works and the design of a much more efficient construction scheduling. The presented new scheduling method leads to a more competitive environment for contraction companies.